2016
DOI: 10.3171/2015.5.jns15233
|View full text |Cite
|
Sign up to set email alerts
|

The GNAQ in the haystack: intramedullary meningeal melanocytoma of intermediate grade at T9–10 in a 58-year-old woman

Abstract: M eningeal melanocytomas are extremely rare tumors originating from leptomeningeal melanocytes. The first reported description, in the early 1970s, was by Limas and Tio.10 Although little is known about this tumor entity as only a few case reports have been published over the past few decades, the tumors mostly occur along the spine and the posterior fossa with a peak incidence around the 5th decade and a slight female predominance. 3,11 According to the classification suggested by Brat et al., 2 melanocytic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Identification of GNAQ G209L facilitated diagnosis in this case. The mutation appears to be pathognomonic for melanocytoma while BRAF-and NRAS-mutations are absent [8,9]. Psammomatous melanotic schwannoma frequently occurs in the context of Carney complex, which needs to be ruled out in such patients [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of GNAQ G209L facilitated diagnosis in this case. The mutation appears to be pathognomonic for melanocytoma while BRAF-and NRAS-mutations are absent [8,9]. Psammomatous melanotic schwannoma frequently occurs in the context of Carney complex, which needs to be ruled out in such patients [10].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of GNAQ G209L facilitated diagnosis in this case. The mutation appears to be pathognomonic for melanocytoma while BRAF‐ and NRAS‐mutations are absent [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, distinguishing between a malignant melanoma, a welldifferentiated melanocytoma, and an intermediate-grade melanocytic lesion [3] remains a diagnostic challenge. Hoffmann et al [7] recently suggested that molecular analysis was the best method for distinguishing between melanocytoma and malignant melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, many case reports have recommended its complete resection. Melanocytoma is generally considered a benign disease but has the potential to recur and become malignant 7,15,16 .…”
Section: Treatmentmentioning
confidence: 99%